Child Passenger Safety in Indonesia - Oos Ariyanto; Setiawan Noerdajasakti; Faizin Sulistio (Invest Journal of Sharia & Economic Law)
Current Indonesian road safety laws, particularly Law No. 22 of 2009 on Traffic and Road Transport, lack specific provisions for the use of child restraint systems, which significantly reduces child passenger safety. Unlike many developed countries with strict regulations that mandate child-specific safety equipment, Indonesian regulations currently mandate only standard seatbelts designed for adults. This inadequacy poses a substantial risk to children because of their physical vulnerability. This study examines the urgency of specific regulations regarding child safety restraints for child passengers in Indonesia. This research employs a normative legal approach to analyze Indonesia's existing legislation alongside international practices. The findings underscore those countries such as the United States, the United Kingdom, and Australia have effectively lowered child accident rates through mandatory child safety restraints and public awareness campaigns. The study concludes that adopting similar practices in Indonesia could enhance child passenger safety, reduce injury rates, and improve overall road safety for young passengers. The implementation of specific child restraint laws and public awareness initiatives are recommended to ensure comprehensive legal protection for child passengers in Indonesia.